Identification of the Problems in Counteracting the Smuggling of Tobacco Products in the Republic of Bulgaria - Tsankova, Gergana (Research Papers, 2022)
The purpose of this study is to identify problems in the policies to combat tobacco smuggling in the Republic of Bulgaria in legal, organizational-coordination, communication, economic and socio-cultural aspects and to propose measures to improve the fight against tobacco smuggling legal, organizational-coordinating, communication, economic and social-cultural aspects, to propose measures to improve the combating of tobacco smuggling in the country and to propose a conceptual model for improving the countermeasures against the smuggling of tobacco products in the Republic of Bulgaria. The model includes not only the processes, but also the participants in it. The purpose of the model is to determine a leading institution in the fight against tobacco smuggling, which will ensure coordination, communication and interaction between the competent state structures in the implementation of measures to fight against smuggling, control the movement of risky goods and cargo on the territory of the country. The proposed new model to improve the existing one is upgraded as the essential elements of the anti-tobacco smuggling system by its participants, reflects in time the internal and external changes of the security environment and related new challenges and socio-economic factors, which have an impact on changing the management system of these processes. The model reflects the information security in the field of international cooperation and the acquisition of information about the changes in the security environment, in relation to the smuggling of tobacco products, the changes in the socio-economic factors that can lead to the stimulation or reduction of the level of this organized crime. This supports the improvement of the organizational-communication aspect as part of the general international and national policy to counter tobacco smuggling, aimed at sharing common resources, planning at the international level and adapting national structures in terms of operational, tactical and technological provision of this counteraction. The research is based on the decomposition and analysis of public policies that implement and contribute to countering tobacco smuggling.
Keywords: Policies; Smuggling; Tobacco products; Countermeasures; Imperfections